Assessment of knowledge of triage among patient attendants presenting in the emergency department: a single center observational study - Dhungana, Rakshya; Bhandari, Rabin; Malla, Gyanendra Bahadur; Chaudhary, Ritesh; Gupta, Pramendra Prasad (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: A triage system is a process by which a clinician assesses a patient’s clinical urgency. Knowledge of the triage systems among patients is not a widely investigated topic in our country and public awareness is lacking. It has been used in BPKIHS since 2003. A study was done to assess knowledge of the triage system inpatient attendants who present to the emergency department in BPKIHS and to describe the knowledge and attitude about triage in the patient attendants. The importance of addressing this issue lies in the fact that increased knowledge of triage systems is associated with a positive attitude in the population towards triage.Method: After ethical approval from IRC, an observational cross-sectional study designed to assess the knowledge of patient attendants was conducted. The sample size was 284, and the sampling was done with convenience sampling. Data was collected using a self-structured questionnaire. Descriptive analysis was performed using a chi-square test for inferential statistics (p 0.05 was considered significant). SPSS 25 was used for statistical analysis.Result: Four item questionnaires were used in 284 patient attendants to determine knowledge. The correct response rate to questions related to information, time to wait before doctor assessment, reason and method were 102(35.8%), 202 (70.6%), 186(65.3%), and 175(61.4 %) respectively. Education and previous visits to the emergency were associated with a positive attitude to triage (p 0.001).Conclusion: The knowledge about the triage in patient attendants was fairly good and patient attendants who know have positive attitude toward the process of triage.